Wyoming proud [large type] - Palmer, Diana (Palmer, Diana. Wyoming men series, 2023)
"It takes one night for Erianne Mitchell to fall heart-first for architect Ty Mosby. But when a devastating mistake tears them apart, Erianne flees to Wyoming with a secret she hopes Ty never discovers. She'll support herself... and the baby growing inside her. How can she be with a man who doesn't trust her? Ty knows exactly what he's lost and he'll do anything to beg for her forgiveness and win back her trust. When he finds her, she's just as proud as he remembers. Is it too late for him to make amends... or is destiny about to test them in an even bigger way?"--